Mapping of Intimate Partner Violence: Evidence From a National Population Survey - Muluneh, Muluken Dessalegn (Journal of interpersonal violence, 2022)
Evidence on the relative importance of geographical distribution and associated factors with intimate partner violence (IPV) can inform regional and national health programs on women?s health. Four thousand seven hundred and twenty married women aged 15-49 years were interviewed in 2016 about IPV and this data was extracted from the Ethiopian Demographic Health Survey (EDHS) in 2020. The sample was selected by a two-staged cluster survey of women. The analysis was conducted using logistic regression that adjusted for clustering and sampling weights. Moreover, weighted proportions of IPV were exported to ArcGIS to conduct autocorrelations to assess the clustering of IPV. Amongst the 4469 married women who were 15 to 49 years of age included in the analysis, 34% (95% CI, 31.4%-36.3%) experienced IPV, 23.5% ( 95% CI, 21.5%-25.7%) experienced physical violence, 10.1% (95% CI, 8.7%- 11.7 %) experienced sexual violence and 24% (95% CI, 21.7%-26.4 %) experienced emotional violence. Partners? controlling behaviour [AOR: 3.94; 95% CI, 3.03- 5.12], partner?s alcohol consumption [AOR: 2.59; 95% CI, 1.80- 3.71], partner educational qualifications [AOR: 2.16; 95% CI, 1.26- 3.71], a woman birthing more than five children [AOR: 1.70; 95% CI, 1.12- 2.56] and a history of the woman?s father being physically violent towards her mother [AOR: 1.99; 95% CI, 1.52- 2.59] were associated with an increased risk of IPV amongst married women in Ethiopia. Western and Central Oromia, Western Amhara, Gambella and Central Tigray and Hararri were identified as hot spot areas in Ethiopia (p<0.001). In this study, there was a significant geographic clustering of IPV in Ethiopia. Controlling and drinking behaviour and partners? unemployment status were identified as important factors for married women experiencing IPV. Hence, there is a need for a context- driven evidence-based design intervention to reduce the impact of IPV.